Perspectives for Using the Programmatic Approach within the Activities of Law Enforcement Agencies of Ukraine - O. O. Khan (Bulletin of Kharkiv National University of Internal Affairs)
On the basis of the analysis of the state of research of algorithms and programming of investigative activity in criminalistics, the author has grounded the expediency of applying a programmatic approach to solving typical tactical problems in other areas of law enforcement activities. Theoretical prerequisites for the development of procedural action programs by law enforcement entities in Ukraine (criminal and procedural, operative and search, administrative and jurisdictional) have been determined. The necessity of intensifying scientific researches in the direction of development of branch concepts of tactics of different types of law enforcement activities and their constituent elements (the concept of tactics, tactical situation, tactical task, tactical technique and system of tactical techniques and their situational predetermination) has been determined. In particular, the author has determined that the investigator is not the only possible subject of being armed with tactical recommendations in the form of algorithms and programs. The subject matter of the research of criminalistic tactics is not only investigative activity, but also operative and search, judicial and prosecutorial activity in criminal proceedings. Equally important is the tactical completion of administrative activities of law enforcement agencies and, on this basis, the establishment of programs of action by police officers, border guards, National Guard, customs service, etc. in exercising their administrative powers for the protection of public order and state border, actions in emergency situations, administrative cases, etc. The justification of the possibility of applying a programmatic approach within administrative activities of law enforcement agencies is the uniformity of administrative and jurisdictional, criminal and procedural activities, which are covered by a single concept of “law enforcement activity”. It has been established that the programmatic approach can be applied in any sphere of law enforcement activity, if: 1) such activity is situational in nature, and it is possible to perform the tasks arising during the implementation of this activity through consistent implementation of certain actions; 2) there is the need to streamline these activities by providing tactical recommendations in the modern form with the use of computer technologies and the ability to use them directly in the course of action, in “field conditions”; 3) the level of elaboration of theoretical bases of tactics of a specific type of law enforcement activity is sufficient (the concept of tactics, tactical situation, tactical task, tactical technique and system of tactical techniques has been elaborated).